THE ROLE OF LEGAL FACTS AS PREREQUISITES FOR THE ORIGIN, EXISTENCE AND TERMINATION OF CRIMINAL LEGAL RELATIONS - Олійник, Олена Сергіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Objective: to clarify the role of legal facts as a prerequisite for the emergence, existence and termination of criminal relations. Research methods: the research was conducted using general scientific methods, such as dialectical analysis and synthesis, abstraction, deduction and induction, and special methods, such as formal law, interpretation of law, comparative law method and others. The empirical basis was the legal acts of Ukraine, scientific works related to this issue. Results: the article clarifies what is the basis (legal fact) that gives rise to criminal law relations. It is determined that the very publication of the criminal law is the same legal fact that gives rise to such relations. It is established that the main features of legal facts are that legal facts: a) are different life circumstances and conditions; b) are defined in the rules of law, more precisely in their hypotheses; c) serve as an indispensable condition for the emergence, change or termination of legal relations; d) entail subjective rights and legal obligations of the parties to the legal relationship; e) are provided by state coercion. It is alleged that the criminal relationship arises in connection with a legal fact - the commission of a criminal offense. It is proved that the normative certainty of legal facts presupposes their establishment in the content of legal norms. Hence, only those life circumstances that are included in the content of the rule of law as an element of the mechanism of legal regulation become important. It is due to this feature that such specific life circumstances are able to influence the solution of a specific social situation and entail certain legal consequences for the participants of criminal-legal social relations. Discussion: study of the role of legal facts as a prerequisite for the emergence, existence and termination of criminal relations.